Potential Effect of Steroidal Alkaloids from Sarcococca saligna against Leishmania tropica - Jan, Naeem Ullah; Ahmad, Bashir; Kifayatullah, Muhammad; Rahim, Haroon; Amin, Fazli (Indian Journal of Pharmaceutical Education and Research, 2019)
Background and Objectives: Sarcococca species have a rich source of steroidal alkaloids that possess different biological and pharmacological activities. Hence, present research was design to isolate the steroidal alkaloid from Sarcococca saligna and to evaluate it for in-vitro antileishmanial activity. Materials and Methods: Compound Holaphylline and Saracodine were isolated through column chromatography followed by spectroscopic techniques for elucidation and were assayed against promastigotes of Leishmania tropica. Results: Saracodine compound eliminates 71.12%, 63.9%, 54.18% and 38.88% of the promastigotes at concentration 100 µM; 75 µM, 50 µM and (25 µM). While, the elimination of promastigotes with compound holaphylline were 82.5%, 76.68%, 65%, 47.22% respectively as compared to untreated group. Conclusion: In present study, compound Holaphylline and Saracodine exhibited inhibition against the promastigotes and justified the claimed medicinal importance of Sarcococca saligna as a remedy for leishmaniasis especially against Leishmania tropica.
Keywords: Sarcococca saligna; Holaphylline; Saracodine; Leishmania tropica; Promastigotes; Chloroform extract